Anaemia prevalence, its determinants and profile of micronutrient status among rural school adolescent girls aged 14–19 years: a cross-sectional study in Nagpur district, Maharashtra, India - Varsha S Dhurde; Archana B Patel; Lindsey M Locks; Patricia L Hibberd (Public Health Nutrition)
Abstract